Complete Genome Sequence of Gordonia rubripertincta SD5, a Soil Bacterium Isolated from a Di-(2-Ethylhexyl) Phthalate-Degrading Enrichment Culture - Han, Sang-Soo (Microbiol Resour Announc, 2020)
We report the complete genome sequence of Gordonia rubripertincta SD5, isolated from a soil-derived di-(2-ethylhexyl) phthalate-degrading enrichment culture. The final genome assembly consists of a 5.10-Mbp chromosome and a plasmid (159 kbp). A total of 4,814 coding sequences were predicted, including 4,741 protein-coding sequences.